Composite nanofiltration membrane as well as preparation method and application thereof

By the ammonium salt group and/or seasonal phosphorus salt base group in the separation layer of the nanoferlin, the problem of low separation efficiency of the existing nanoferlin magnesium lithium lithium is solved, and the high magnesium lithium separation coefficient and Taking into account the high water flux.

CN119368027AActive Publication Date: 2025-01-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310934843.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-01-28
Estimated Expiration
2043-07-27

AI Technical Summary

Technical Problem

Existing commercial nanofiltration membranes are inefficient in magnesium-lithium separation and cannot effectively extract pure lithium resources from salt lake water.

Method used

By connecting the monsoon ammonium salt group and/or the monsoon phosphorus salt group in the separation layer of the nanoferlin, improve the positive charge density of the membrane, thereby using the exclusion effect of positive charge to improve the separation efficiency of magnesium lithium.

Benefits of technology

While maintaining high water flux, it has significantly improved the separation coefficient of magnesium and lithium, and is suitable for the field of water treatment separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368027A_ABST
    Figure CN119368027A_ABST
Patent Text Reader

Abstract

The invention relates to the field of membranes, and discloses a composite nanofiltration membrane and a preparation method and application thereof, the composite nanofiltration membrane sequentially comprises a bottom layer, a porous support layer and a polyamide separation layer; wherein the polyamide separation layer is grafted with a quaternary ammonium salt group and / or a quaternary phosphonium salt group through N atoms; the quaternary ammonium salt group has a structure as shown in a formula I; the quaternary phosphonium salt group has a structure as shown in a formula II and / or a formula III; the separation layer of the composite nanofiltration membrane is grafted with a specific quaternary ammonium salt group and / or a quaternary phosphonium salt group, so that the composite nanofiltration membrane has a high magnesium-lithium separation coefficient while keeping high water flux, and is particularly suitable for the field of water treatment separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of membranes, and in particular to a composite nanofiltration membrane and a preparation method and application thereof. Background Art

[0002] In recent years, with the widespread application of new energy vehicles, the demand for lithium energy has gradually increased. In my country, most lithium resources are stored in salt lake brine. In addition to lithium ions, salt lake water also contains a large amount of magnesium ions and sodium ions. Therefore, it is very technically difficult to extract pure lithium resources from salt lakes. Researchers have developed a series of methods and processes such as precipitation, solar pond, extraction, calcination, membrane separation and adsorption to obtain lithium resources. Among them, membrane separation and adsorption are the most widely studied.

[0003] Existing commercial nanofiltration membranes are not designed for magnesium-lithium separation. Their separation efficiency for magnesium ions and lithium ions is very low (magnesium-lithium separation coefficient is less than 5), and they cannot be used for lithium extraction from salt lakes. In recent years, a large number of scientific studies have shown that increasing the positive charge density on the surface of the nanofiltration membrane separation layer can increase the membrane's retention rate for magnesium chloride through the Donan effect, thereby improving the magnesium-lithium separation efficiency. The vast majority of research is still in the laboratory stage, and the magnesium-lithium separation coefficient of the prepared nanofiltration membrane with a positive charge on the surface is still less than 20. Therefore, how to use nanofiltration membranes to achieve efficient magnesium-lithium separation still faces many challenges.

[0004] In addition, positively charged nanofiltration membranes also have important applications in the treatment of electroplating wastewater. As an emerging process membrane material, the application of positively charged nanofiltration membranes will become more and more extensive. Summary of the invention

[0005] The purpose of the present invention is to overcome the disadvantage of low magnesium-lithium separation efficiency of existing nanofiltration membranes, and to provide a composite nanofiltration membrane with a high magnesium-lithium separation coefficient and a preparation method and application thereof. Specific quaternary ammonium salt groups and / or quaternary phosphonium salt groups are grafted into the separation layer of the composite nanofiltration membrane, so that the composite nanofiltration membrane has a high magnesium-lithium separation coefficient while maintaining a high water flux, and is particularly suitable for the field of water treatment separation.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composite nanofiltration membrane, wherein the composite nanofiltration membrane comprises a bottom layer, a porous support layer and a polyamide separation layer in sequence;

[0007] Wherein, the polyamide separation layer is grafted with quaternary ammonium salt groups and / or quaternary phosphonium salt groups via N atoms; the quaternary ammonium salt groups have the structure shown in formula I; the quaternary phosphonium salt groups have the structure shown in formula II and / or formula III;

[0008]

[0009] Among them, R 1 is a C1-C9 substituted or unsubstituted alkylene group; R 2 , R 3 and R 4 R is independently selected from C1-C3 alkyl or phenyl; 5 is a C1-C6 alkylene group, a phenyl group or a C7-C10 aralkyl group; R 6 , R 7 and R 8 Each is independently phenyl or C7-C10 aralkyl; R 9 , R 10 and R 11 Each is independently a phenyl group or a C7-C10 aralkyl group, and n is an integer of 0-3;

[0010] X, X 1 and X 2 are each independently halogen.

[0011] A second aspect of the present invention provides a method for preparing a composite nanofiltration membrane, wherein the preparation method comprises the following steps:

[0012] S1. Under stirring, dropwise adding a first solution containing a quaternary ammonium halogenate salt and / or a quaternary phosphonium halogenate salt and a catalyst into a second solution containing a polyamine to react and obtain a modified polyamine;

[0013] S2, preparing a porous supporting layer on the bottom layer;

[0014] S3, bringing the surface of the porous support layer into first contact with the aqueous phase containing the modified polyamine in step S1, and then bringing it into second contact with the organic phase containing polyacyl chloride, and then subjecting it to heat treatment to obtain the composite nanofiltration membrane;

[0015] The halogenated quaternary ammonium salt has a structure shown in Formula IV; the halogenated quaternary phosphonium salt has a structure shown in Formula V or VI;

[0016]

[0017] Among them, R 1 ' is a C1-C9 substituted or unsubstituted alkylene group; R 2 '、R 3 ' and R 4 ' are each independently selected from C1-C3 alkyl or phenyl; R 5 ' is a C1-C6 alkylene group, a phenyl group or a C7-C10 aralkyl group; R 6 '、R 7 ' and R 8 ' are each independently phenyl or C7-C10 aralkyl; n is an integer of 0-3; R9 '、R 10 ' and R 11 'Each independently is phenyl or C7-C10 aralkyl;

[0018] X1, X2, X3 and X are each independently halogen.

[0019] The third aspect of the present invention provides a composite nanofiltration membrane prepared by the above preparation method.

[0020] A fourth aspect of the present invention provides an application of the above-mentioned composite nanofiltration membrane in the field of water treatment and separation.

[0021] Through the above technical solution, the composite nanofiltration membrane provided by the present invention and its preparation method and application can achieve the following beneficial effects:

[0022] The separation layer of the composite nanofiltration membrane provided by the present invention is grafted with specific quaternary ammonium salt groups and / or quaternary phosphonium salt groups, so that the positive charge density of the composite nanofiltration membrane is significantly improved, and the repulsive effect between the positive charges is utilized to improve the interception effect of the composite nanofiltration membrane on magnesium ions, thereby improving the magnesium-lithium separation efficiency of the composite nanofiltration membrane while maintaining a high water flux of the composite nanofiltration membrane.

[0023] The preparation method of the composite nanofiltration membrane provided by the present invention comprises the following steps: subjecting a halogenated quaternary ammonium salt and / or a halogenated quaternary phosphonium salt to a biochemical reaction with a polyamine under the action of an alkaline catalyst to obtain a positively charged modified polyamine, and after interfacial polymerization, the surface positive charge density of the composite nanofiltration membrane is significantly improved, and the repulsive effect between the positive charges is utilized to improve the interception effect of the composite nanofiltration membrane on magnesium ions, thereby improving the magnesium-lithium separation efficiency of the composite nanofiltration membrane while maintaining a high water flux of the composite nanofiltration membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the reaction of 2-bromoethyltrimethylammonium bromide with amino groups (primary amines, secondary amines and tertiary amines) on the surface of the polyamide separation layer in Example 1 of the present invention;

[0025] Figure 2 The infrared spectra of the membrane separation layer of the composite nanofiltration membrane of Example 1 and Comparative Example 1;

[0026] Figure 3 This is the membrane surface XPS spectrum of the composite nanofiltration membrane of Example 1;

[0027] Figure 4 This is the membrane surface XPS spectrum of the composite nanofiltration membrane of Comparative Example 1;

[0028] Figure 5 Schematic diagram of the reaction of bromopropyltriphenylphosphonium bromide with amino groups (primary amines, secondary amines and tertiary amines) on the surface of the polyamide separation layer in Example 7 of the present invention;

[0029] Figure 6 The infrared spectra of the composite nanofiltration membranes of Example 7 and Comparative Example 1;

[0030] Figure 7 This is the XPS spectrum of the composite nanofiltration membrane of Example 7. DETAILED DESCRIPTION

[0031] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0032] The first aspect of the present invention provides a composite nanofiltration membrane, wherein the composite nanofiltration membrane comprises a bottom layer, a porous support layer and a polyamide separation layer in sequence;

[0033] Wherein, the polyamide separation layer is grafted with quaternary ammonium salt groups and / or quaternary phosphonium salt groups via N atoms;

[0034] The quaternary ammonium salt group has a structure shown in Formula I; the quaternary phosphonium salt group has a structure shown in Formula II and / or Formula III;

[0035]

[0036] Among them, R 1 is a C1-C9 substituted or unsubstituted alkylene group; R 2 , R 3 and R 4 R is independently selected from C1-C3 alkyl or phenyl; 5 is a C1-C6 alkylene group, a phenyl group or a C7-C10 aralkyl group; R 6 , R 7 and R 8 Each is independently phenyl or C7-C10 aralkyl; R 9 , R 10 and R 11 Each is independently a phenyl group or a C7-C10 aralkyl group, and n is an integer of 0-3;

[0037] X, X 1 and X 2 are each independently halogen.

[0038] In the present invention, * refers to the quaternary ammonium salt group or quaternary phosphonium salt group and the -NH-, The location where the connection is made into a bond.

[0039] In the present invention, X 1 , X 2 , X 3 and X are only used to distinguish different substituents and have no particular limiting meaning.

[0040] In the present invention, specific quaternary ammonium salt groups and / or quaternary phosphonium salt groups are grafted into the separation layer of the composite nanofiltration membrane, so that the composite nanofiltration membrane has a high magnesium-lithium separation coefficient while maintaining a high water flux, and is particularly suitable for the field of water treatment separation.

[0041] In the present invention, R 1 It may be a branched chain alkylene group or a linear chain alkylene group.

[0042] Furthermore, R 1 is a C1-C6 substituted or unsubstituted alkylene or phenyl group, R 2 , R 3 and R 4 Each independently is CH 3 ; R 5 is a C1-C3 alkylene group, a phenyl group or a C8-C9 aralkyl group; R 6 , R 7 and R 8 are each independently phenyl; R 9 , R 10 and R 11 Each is independently a phenyl group, and n is an integer of 0-3.

[0043] In a specific embodiment of the present invention, R 1 It is a C1-C3 substituted alkylene group, wherein the substituent is a hydroxyl group or a carboxyl group.

[0044] Furthermore, X is Cl, Br or I, X 1 and X 2 are each independently F, Cl, Br or I.

[0045] In one embodiment of the present invention, in Formula I, R 1 For ethylene, Propylene, butylene, pentylene or hexylene; R 2 , R 3 and R 4 is methyl, ethyl or phenyl; X is Cl, Br or I.

[0046] In one embodiment of the present invention, Formula II, R 5 is propylene, ethylene, methylene or R 6 , R 7 and R 8 is phenyl; X is Cl, Br or I.

[0047] According to the present invention, the content of nitrogen atoms in the quaternary ammonium salt groups in the composite nanofiltration membrane is 1-5 at.%.

[0048] In the present invention, when the content of nitrogen atoms in the quaternary ammonium salt groups in the composite nanofiltration membrane meets the above range, the composite nanofiltration membrane has a high surface electrode potential and a small average pore size, so that the composite nanofiltration membrane has a high magnesium-lithium separation coefficient.

[0049] Furthermore, the content of nitrogen atoms in the composite nanofiltration membrane is 2-5 at.%.

[0050] According to the present invention, the content of phosphorus atoms in the composite nanofiltration membrane is 0.4-3 at.%.

[0051] In the present invention, when the content of phosphorus atoms in the composite nanofiltration membrane meets the above range, the composite nanofiltration membrane has a high surface electrode potential and a small average pore size, so that the composite nanofiltration membrane has a high magnesium-lithium separation coefficient.

[0052] Furthermore, the content of phosphorus atoms in the composite nanofiltration membrane is 0.5-2 at.%.

[0053] According to the present invention, the surface Zeta potential of the composite nanofiltration membrane is -5mV to 15mV.

[0054] In the present invention, when the surface Zeta potential of the composite nanofiltration membrane satisfies the above range, it indicates that the composite nanofiltration membrane has a high surface electrode potential. When it is used for magnesium-lithium separation, it can better repel divalent magnesium ions, making it difficult for magnesium ions in the liquid to pass through the separation membrane, while allowing monovalent lithium ions to pass as much as possible, thereby obtaining a higher magnesium-lithium separation efficiency.

[0055] In the present invention, the surface Zeta potential of the composite nanofiltration membrane refers to the surface Zeta potential at pH=7.

[0056] Furthermore, the surface Zeta potential of the composite nanofiltration membrane is 0 mV to 10 mV.

[0057] According to the present invention, the average pore size of the composite nanofiltration membrane is 0.1-0.5 nm.

[0058] In the present invention, when the average pore size of the composite nanofiltration membrane meets the above range, it indicates that the composite nanofiltration membrane has a high density. When it is used for magnesium-lithium separation, it can better retain divalent magnesium ions, making it difficult for magnesium ions in the liquid to pass through the separation membrane, while allowing monovalent lithium ions to pass as much as possible, thereby obtaining a higher magnesium-lithium separation efficiency.

[0059] Furthermore, the average pore size of the composite nanofiltration membrane is 0.15-0.35 nm.

[0060] According to the present invention, the contact angle of the composite nanofiltration membrane is 30-80°.

[0061] In the present invention, the composite nanofiltration membrane has a contact angle within the range of the present invention, which indicates that the composite nanofiltration membrane has excellent hydrophilicity and can make the composite nanofiltration membrane have excellent water permeability.

[0062] Furthermore, the contact angle of the composite nanofiltration membrane is 30-60°.

[0063] In the present invention, the bottom layer and the porous support layer are not specifically limited, and can be made of various existing materials that have a certain strength and can be used for nanofiltration and reverse osmosis membranes.

[0064] In the present invention, the bottom layer is a non-woven fabric material, preferably polyester and / or polyethylene.

[0065] In the present invention, the porous support layer material may be at least one of polyethersulfone, polysulfone, polyarylether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone.

[0066] In the present invention, the polyamide separation layer is produced by interfacial polymerization of polyamine modified by quaternary ammonium halogenate salt and / or quaternary phosphonium halogenate salt and polyacyl chloride.

[0067] In the present invention, the polyamine is selected from at least one of polyethyleneimine, polyethyleneamine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, polyethylenepolyamine, piperazine, m-phenylenediamine and p-phenylenediamine, preferably polyethyleneimine and / or polyethylenepolyamine.

[0068] In the present invention, the polyacid chloride is selected from at least one of 1,3,5-benzenetricarboxylic acid chloride, 1,2-phthaloyl chloride, 1,3-phthaloyl chloride, 1,4-phthaloyl chloride and adipoyl chloride, preferably 1,3,5-benzenetricarboxylic acid chloride and / or 1,4-phthaloyl chloride.

[0069] In the present invention, the halogenated quaternary ammonium salt has a structure shown in Formula IV;

[0070]

[0071] Among them, R 1 ' is a C1-C9 substituted or unsubstituted alkylene group; R 2 '、R 3 ' and R 4 ' are each independently selected from C1-C3 alkyl or phenyl; X 1 and X are each independently halogen.

[0072] Furthermore, R1 ' is a C1-C6 substituted or unsubstituted alkylene or phenyl; R 2 '、R 3 ' and R 4 'Each independently is CH 3 ; X is Cl, Br or I; X 1 is F, Cl, Br or I.

[0073] In a specific embodiment of the present invention, R 1 ' is a C1-C3 substituted alkylene group, wherein the substituent is a hydroxyl group or a carboxyl group, preferably a hydroxyl group.

[0074] In a specific embodiment of the present invention, the halogenated quaternary ammonium salt is selected from at least one of 2-chloroethyltrimethylammonium chloride, 2-chloroethyltriethylammonium chloride, 2-chloroethyltriphenylammonium chloride, 3-chloro-2-hydroxypropyltrimethylammonium chloride, 3-chloropropyltrimethylammonium chloride, 4-chlorobutyltrimethylammonium chloride, 5-chloropentyltrimethylammonium chloride, 6-chlorohexyltrimethylammonium chloride, 2-bromoethyltrimethylammonium bromide, 3-bromopropyltrimethylammonium bromide, 4-bromobutyltrimethylammonium bromide, 5-bromopentyltrimethylammonium bromide, 6-bromohexyltrimethylammonium bromide, iodomethyltrimethylammonium iodide, 2-iodoethyltrimethylammonium iodide, 3-iodopropyltrimethylammonium iodide, 4-iodobutyltrimethylammonium iodide, 5-iodopentyltrimethylammonium iodide and 6-iodohexyltrimethylammonium iodide.

[0075] In the present invention, the halogenated quaternary phosphonium salt has a structure shown in Formula V or VI;

[0076]

[0077] Among them, R 5 ' is a C1-C6 alkylene group, a phenyl group or a C7-C10 aralkyl group; R 6 '、R 7 ' and R 8 ' are each independently phenyl or C7-C10 aralkyl; n is an integer of 0-3; R 9 '、R 10 ' and R 11 'Each independently is phenyl or C7-C10 aralkyl;

[0078] X 1 , X 2 , X 3 and X are each independently halogen.

[0079] Furthermore, R 5 ' is a C1-C3 alkylene group, a phenyl group or a C8-C9 aralkyl group; R 6 '、R 7 ' and R8 ' are each independently phenyl; n is an integer of 0-3; R 9 '、R 10 ' and R 11 ' are each independently phenyl; X is Cl, Br or I; X 1 , X 2 and X 3 are each independently F, Cl, Br or I.

[0080] In a specific embodiment of the present invention, the halogenated quaternary phosphonium salt is selected from 3-bromopropyl triphenyl phosphonium bromide, 2-bromoethyl triphenyl phosphonium bromide, 1-bromoethyl triphenyl phosphonium bromide, bromomethyl triphenyl phosphonium bromide, 3-chloropropyl triphenyl phosphonium chloride, 2-chloroethyl triphenyl phosphonium chloride, 1-chloroethyl triphenyl phosphonium chloride, chloromethyl triphenyl phosphonium chloride, 3-iodopropyl triphenyl phosphonium iodide, 2-iodoethyl triphenyl phosphonium iodide, 1-iodoethyl triphenyl phosphonium iodide, iodomethyl triphenyl phosphonium bromide, (3,3,3-trichloropropyl) triphenyl phosphonium chloride, 4-bromomethylbenzyl triphenyl phosphonium bromide (R5' is -CH 2 -Benzene-CH 2 -), (bromodifluoromethyl)triphenylphosphonium bromide (n=0), 2-bromomethylbenzyltriphenylphosphonium bromide (R5' is -CH 2 -Benzene-CH 2 -), 3-bromomethylbenzyltriphenylphosphonium bromide (R5' is -CH 2 -Benzene-CH 2 -), 4-chloromethylbenzyltriphenylphosphonium chloride (R5' is -CH 2 -Benzene-CH 2 -), 2-chloromethylbenzyltriphenylphosphonium chloride (R5' is -CH 2 -Benzene-CH 2 -), 3-chloromethylbenzyltriphenylphosphonium chloride (R5' is -CH 2 -Benzene-CH 2 -), 4-iodomethylbenzyltriphenylphosphonium iodide (R5' is -CH 2 -Benzene-CH 2 -), at least one of 2-iodomethylbenzyltriphenylphosphonium iodide and 3-iodomethylbenzyltriphenylphosphonium iodide, preferably 3-bromopropyltriphenylphosphonium bromide and / or 4-bromomethylbenzyltriphenylphosphonium bromide.

[0081] According to the present invention, the thickness of the bottom layer, the porous support layer, and the polyamide separation layer is not particularly limited, and can be a conventional choice in the art. However, in order to enable the three layers to play a better synergistic role, the obtained composite nanofiltration membrane can better have an excellent magnesium-lithium separation coefficient and a higher water flux. Preferably, the thickness of the bottom layer is 30-150 μm, preferably 50-120 μm; the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm; the thickness of the polyamide separation layer is 10-500 nm, preferably 50-300 nm.

[0082] A second aspect of the present invention provides a method for preparing a composite nanofiltration membrane, wherein the preparation method comprises the following steps:

[0083] S1. Under stirring, adding a first solution containing a quaternary ammonium halogenate salt and / or a quaternary phosphonium halogenate salt and a catalyst to a second solution containing a polyamine to react and obtain a modified polyamine;

[0084] S2, preparing a porous supporting layer on the bottom layer;

[0085] S3, bringing the surface of the porous support layer into first contact with the aqueous phase containing the modified polyamine in step S1, and then bringing it into second contact with the organic phase containing polyacyl chloride, and then subjecting it to heat treatment to obtain the composite nanofiltration membrane;

[0086] The halogenated quaternary ammonium salt has a structure shown in Formula IV; the halogenated quaternary phosphonium salt has a structure shown in Formula V or VI;

[0087]

[0088] Among them, R 1 ' is a C1-C9 substituted or unsubstituted alkylene group; R 2 '、R 3 ' and R 4 ' are each independently selected from C1-C3 alkyl or phenyl; R 5 ' is a C1-C6 alkylene group, a phenyl group or a C7-C10 aralkyl group; R 6 '、R 7 ' and R 8 ' are each independently phenyl or C7-C10 aralkyl; n is an integer of 0-3; R 9 '、R 10 ' and R 11 'Each independently is phenyl or C7-C10 aralkyl;

[0089] X 1 , X 2 , X 3 and X are each independently halogen.

[0090] In the present invention, a halogenated quaternary ammonium salt and / or a halogenated quaternary phosphonium salt is subjected to a biochemical reaction with a polyamine under the action of an alkaline catalyst to obtain a positively charged modified polyamine, and after interfacial polymerization, the surface positive charge density of the composite nanofiltration membrane is significantly improved, and the repulsive effect between the positive charges is utilized to improve the interception effect of the composite nanofiltration membrane on magnesium ions, thereby improving the magnesium-lithium separation efficiency of the composite nanofiltration membrane while maintaining a high water flux of the composite nanofiltration membrane.

[0091] Furthermore, R 1 ' is a C1-C6 substituted or unsubstituted alkylene group; R 2 '、R 3 ' and R 4 'Each independently is CH 3 ; R 5 ' is a C1-C3 alkylene group, a phenyl group or a C8-C9 aralkyl group; R 6 '、R 7 ' and R 8 ' are each independently phenyl; n is an integer of 0-3; R 9 '、R 10 ' and R 11 ' are each independently phenyl.

[0092] Furthermore, R 1 ' is a C1-C3 substituted alkylene group, wherein the substituent is a hydroxyl group or a carboxyl group, preferably a hydroxyl group.

[0093] Furthermore, X is Cl, Br or I.

[0094] Furthermore, X 1 , X 2 and X 3 are each independently F, Cl, Br or I.

[0095] According to the present invention, the halogenated quaternary ammonium salt is selected from at least one of 2-chloroethyltrimethylammonium chloride, 2-chloroethyltriethylammonium chloride, 2-chloroethyltriphenylammonium chloride, 3-chloro-2-hydroxypropyltrimethylammonium chloride, 3-chloropropyltrimethylammonium chloride, 4-chlorobutyltrimethylammonium chloride, 5-chloropentyltrimethylammonium chloride, 6-chlorohexyltrimethylammonium chloride, 2-bromoethyltrimethylammonium bromide, 3-bromopropyltrimethylammonium bromide, 4-bromobutyltrimethylammonium bromide, 5-bromopentyltrimethylammonium bromide, 6-bromohexyltrimethylammonium bromide, iodomethyltrimethylammonium iodide, 2-iodoethyltrimethylammonium iodide, 3-iodopropyltrimethylammonium iodide, 4-iodobutyltrimethylammonium iodide, 5-iodopentyltrimethylammonium iodide and 6-iodohexyltrimethylammonium iodide.

[0096] According to the present invention, the halogenated quaternary phosphonium salt is selected from 3-bromopropyl triphenyl phosphonium bromide, 2-bromoethyl triphenyl phosphonium bromide, 1-bromoethyl triphenyl phosphonium bromide, bromomethyl triphenyl phosphonium bromide, 3-chloropropyl triphenyl phosphonium chloride, 2-chloroethyl triphenyl phosphonium chloride, 1-chloroethyl triphenyl phosphonium chloride, chloromethyl triphenyl phosphonium chloride, 3-iodopropyl triphenyl phosphonium iodide, 2-iodoethyl triphenyl phosphonium iodide, 1-iodoethyl triphenyl phosphonium iodide, iodomethyl triphenyl phosphonium bromide, (3,3,3-trichloropropyl) triphenyl phosphonium chloride, 4-bromo At least one of methylbenzyltriphenylphosphonium bromide, (bromodifluoromethyl)triphenylphosphonium bromide, 2-bromomethylbenzyltriphenylphosphonium bromide, 3-bromomethylbenzyltriphenylphosphonium bromide), 4-chloromethylbenzyltriphenylphosphonium chloride, 2-chloromethylbenzyltriphenylphosphonium chloride, 3-chloromethylbenzyltriphenylphosphonium chloride, 4-iodomethylbenzyltriphenylphosphonium iodide, 2-iodomethylbenzyltriphenylphosphonium iodide and 3-iodomethylbenzyltriphenylphosphonium iodide; preferably 3-bromopropyltriphenylphosphonium bromide and / or 4-bromomethylbenzyltriphenylphosphonium bromide.

[0097] According to the present invention, the concentration of the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the first solution is 0.5 wt %-20 wt %.

[0098] In the present invention, when the concentration of halogenated quaternary ammonium salt and / or halogenated quaternary phosphonium salt in the first solution in the control step S1 satisfies the above-mentioned range, it is possible to ensure that the halogenated quaternary ammonium salt and / or halogenated quaternary phosphonium salt of the first solution can fully react with the polyamine in the second solution, introduce more quaternary phosphonium salts and / or quaternary ammonium salt structures in the polyamine, and ensure that the composite nanofiltration membrane maintains a high water flux. Specifically, if the concentration of halogenated quaternary ammonium salt and / or halogenated quaternary phosphonium salt in the first solution is too low, when reacting with the polyamine, it is impossible to introduce enough quaternary ammonium salt structures and / or quaternary phosphonium salt structures on the polyamine, if the concentration of halogenated quaternary ammonium salt and / or halogenated quaternary phosphonium salt in the first solution is too high, the reactive amino groups in the polyamine will be excessively consumed, resulting in a decrease in the density of the polyamide separation layer, affecting the water flux of the composite nanofiltration membrane.

[0099] Furthermore, the concentration of the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the first solution is 1 wt%-10 wt%.

[0100] According to the present invention, the catalyst is selected from at least one of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, potassium bicarbonate, disodium hydrogen phosphate and dipotassium hydrogen phosphate, preferably potassium hydroxide.

[0101] According to the present invention, the concentration of the catalyst in the first solution is 0.01 wt%-5 wt%.

[0102] In the present invention, when the concentration of the catalyst in the first solution in step S1 is controlled to meet the above range, it can ensure that the halogenated quaternary ammonium salt and / or halogenated quaternary phosphonium salt in the first solution can fully react with the polyamine in the second solution and have a high reaction rate, and the quaternary ammonium salt and / or quaternary phosphonium salt structure is introduced into the molecular structure of the polyamine in a relatively short time.

[0103] Furthermore, the concentration of the catalyst in the first solution is 0.1 wt%-1 wt%.

[0104] According to the present invention, in step S1, the polyamine is selected from at least one of polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, polyethylenepolyamine, piperazine, m-phenylenediamine and p-phenylenediamine; preferably polyethyleneimine and / or polyethylenepolyamine.

[0105] According to the present invention, the concentration of the polyamine in the second solution is 1 wt%-20 wt%, preferably 5 wt%-10 wt%.

[0106] According to the present invention, the amounts of the first solution and the second solution are such that the mass ratio of the polyamine, the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt, and the catalyst is 1-500:1-100:1.

[0107] In the present invention, when the mass ratio of the polyamine, the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt and the catalyst is controlled to meet the above range, it can be ensured that the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the first solution can fully react with the polyamine in the second solution, and the reaction rate and reaction efficiency are both high, and more quaternary phosphonium salt and / or quaternary ammonium salt structures can be introduced into the polyamine in a relatively short time.

[0108] Furthermore, the amounts of the first solution and the second solution are such that the mass ratio of the polyamine, the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt, and the catalyst is 1-200:1-50:1.

[0109] According to the present invention, in step S1, the reaction conditions include: reaction temperature of 25-90° C.; reaction time of 1-48 h.

[0110] In the present invention, when the conditions for controlling the reaction in step S1 satisfy the above range, it can ensure that the halogenated quaternary ammonium salt and / or halogenated quaternary phosphonium salt in the first solution can fully react with the polyamine in the second solution, and the reaction rate and reaction efficiency are both high, and more quaternary phosphonium salt and / or quaternary ammonium salt structures can be introduced into the polyamine in a shorter time.

[0111] Furthermore, in step S1, the reaction conditions include: reaction temperature of 40-60°C; reaction time of 6-24h.

[0112] In a preferred embodiment of the present invention, the first solution is added dropwise to the second solution containing the polyamine. By adding the first solution dropwise to the second solution containing the polyamine, the reaction rate can be controlled, and the first solution and the second solution are fully mixed to ensure that the quaternary ammonium halogenide and / or the quaternary phosphonium halogenide reacts fully with the polyamine.

[0113] According to the present invention, the dropping speed is 0.5-5 mL / min, preferably 1-3 mL / min.

[0114] In the present invention, there is no particular limitation on the method for preparing the porous supporting layer in the bottom layer in step S2, and it can be prepared by conventional methods in the art, preferably by a phase inversion method. Specifically, a polymer solution of the porous supporting layer material is coated on one surface of the bottom layer, and the porous supporting layer is obtained by phase inversion.

[0115] In the present invention, the phase inversion method can preferably be: dissolving the supporting layer polymer material in a solvent to obtain a polymer solution with a concentration of 10-20 weight %, and degassing at 20-40°C for 10-180min; then coating the polymer solution on the bottom layer to obtain an initial membrane, and then soaking it in water at a temperature of 10-30°C for 10-60min to obtain the supporting layer polymer porous membrane through the phase inversion layer.

[0116] The solvent may be N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, or the like.

[0117] In the present invention, the polyamide separation layer is produced by interfacial polymerization of polyamine modified by quaternary ammonium halogenate salt and / or quaternary phosphonium halogenate salt and polyacyl chloride.

[0118] According to the present invention, the polyacid chloride is selected from at least one of 1,3,5-benzenetricarboxylic acid chloride, 1,2-phthaloyl chloride, 1,3-phthaloyl chloride, 1,4-phthaloyl chloride and adipoyl chloride, preferably 1,3,5-benzenetricarboxylic acid chloride and / or 1,4-phthaloyl chloride.

[0119] According to the present invention, the concentration of the modified polyamine in the aqueous phase is 0.1 wt%-5 wt%, preferably 0.5 wt%-2 wt%.

[0120] According to the present invention, the concentration of the polyacid chloride in the organic phase is 0.01 wt%-1 wt%, preferably 0.1-0.5 wt%.

[0121] In the present invention, there is no particular limitation on the type of the solvent of the organic phase, as long as it can dissolve the polyacyl chloride. Preferably, the solvent of the organic phase is one or more of n-hexane, dodecane, n-heptane, and alkane solvent oil (Isopar E, Isopar G, Isopar H, Isopar L, and Isopar M).

[0122] In the present invention, in step S3, there is no special limitation on the conditions for the interfacial polymerization between the modified polyamine and the polyacid chloride, and it can be carried out according to conventional conditions in the art. However, in order to enable the three layers to play a better synergistic role and enable the obtained composite nanofiltration membrane to better have an excellent magnesium-lithium separation coefficient and a higher water flux, preferably, the first contact time is 5-100s, preferably 10-60s; the second contact time is 10-200s, preferably 20-120s; the heat treatment conditions include: the heat treatment temperature is 40-150°C, preferably 50-120°C; the heat treatment time is 0.5-10min, preferably 1-5min.

[0123] In the present invention, in step S3, the ratio of the volume of the aqueous phase containing the modified polyamine to the membrane area of ​​the porous support layer is 0.05-1 mL / cm 2 The ratio of the volume of the organic phase containing polyacyl chloride to the membrane area of ​​the porous support layer is 0.01-0.5 mL / cm 2 .

[0124] The third aspect of the present invention provides a composite nanofiltration membrane prepared by the above preparation method.

[0125] A fourth aspect of the present invention provides an application of the above-mentioned composite nanofiltration membrane in the field of water treatment and separation.

[0126] Other features and advantages of the present invention will be described in detail in the following detailed description.

[0127] The present invention will be described in detail below through examples.

[0128] In the following examples and comparative examples:

[0129] (1) The water flux of the composite nanofiltration membrane is tested by the following method: the separation membrane is placed in a membrane pool, the water permeation of the separation membrane is measured under the conditions of 0.5 MPa and a temperature of 25° C. within a certain period of time, and the water flux is calculated by the following formula:

[0130] J = Q / (A·t), where J is the water flux, Q is the water permeation (L), and A is the effective membrane area of ​​the separation membrane (m 2 ), t is time (h).

[0131] (2) The desalination rate of the composite nanofiltration membrane was tested by the following method: the composite separation membrane was placed in a membrane pool, the original aqueous solution was 2000 ppm magnesium chloride or 2000 ppm lithium chloride, and after pre-pressing at 0.2 MPa for 0.5 h, the permeate was obtained at a pressure of 0.5 MPa, and the concentrations of magnesium chloride and lithium chloride in the permeate were measured by a conductivity meter, and the desalination rate was calculated by the following formula:

[0132] R=(C p -C f ) / C p ×100%, where R is the desalination rate, C p is the concentration of magnesium chloride or lithium chloride in the original solution (measured by conductivity meter), C f is the concentration of magnesium chloride or lithium chloride in the permeate (measured by conductivity meter);

[0133] (3) The magnesium-lithium separation coefficient of the composite nanofiltration membrane was obtained by testing the following method: the composite separation membrane was placed in a membrane pool, the original aqueous solution was a mixture of 2000 ppm magnesium chloride and 100 ppm lithium chloride, and after pre-pressing at 0.2 MPa for 0.5 h, the permeate was obtained at a pressure of 0.5 MPa.

[0134] The magnesium-lithium separation coefficient is calculated by the following formula:

[0135] Where S is the magnesium-lithium separation coefficient, C Li,p and C Li,f are the concentrations of lithium ions in the permeate and raw material solution (measured by ion chromatography); C Mg,p and C Mg,f are the concentrations of magnesium ions in the permeate and raw solution (measured by ion chromatography), respectively.

[0136] (4) Surface contact angle measurement of composite nanofiltration membrane

[0137] The surface contact angle of the composite film sample was tested by the sessile drop method using a DSA100 surface contact angle meter produced by KRUSS, Germany. Before the test, the sample was dried in a vacuum oven at 60°C for 30 minutes to remove surface and internal moisture, and then the dried film was attached to a flat glass slide with double-sided tape. The volume of each water droplet during the test was 2 μL. The water droplet was dropped on the film surface for 3 seconds and then tested immediately. The average value was taken after multiple measurements to determine the final contact angle.

[0138] (5) Determination of the content of nitrogen atoms and phosphorus atoms in the quaternary ammonium salt groups on the surface of composite nanofiltration membranes:

[0139] Before measurement, the sample was dried in an oven to constant weight, and the elemental composition of the surface of the composite film sample was determined using a Sigma Probe X-ray photoelectron spectrometer produced by Thermo VG, UK. For samples containing quaternary ammonium salt groups, the molar content of nitrogen atoms in the quaternary ammonium salt groups was calculated by the ratio of the quaternary ammonium nitrogen peak area to the total nitrogen atom peak area in the nitrogen atom fine spectrum, and the calculation formula is as follows; the content of phosphorus atoms can be directly measured by XPS spectra.

[0140] Among them C N+ is the atomic percentage content (at.%) of quaternary amine nitrogen, C N is the total percentage of nitrogen atoms (at.%), S N+ is the peak area of ​​quaternary amine nitrogen in the XPS spectrum, S N is the total peak area of ​​nitrogen atoms in the XPS spectrum.

[0141] (6) Surface total reflection infrared spectroscopy characterization of composite nanofiltration membrane (ATR-FTIR)

[0142] Before testing, the samples were dried in an oven to constant weight, and the infrared spectra of the composite reverse osmosis membrane and related modified samples were measured using attenuated total reflection infrared (ATR-FTIR) spectroscopy. A Fourier transform infrared spectrometer (Nicolet 6700, USA; ATR accessory, PIKE ATRMaxⅡ, incident angle 50 degrees, internal reflection chip ZnSe, n = 2.43) was used to measure the infrared spectra of the composite reverse osmosis membrane and related modified samples.

[0143] (7) Pore size test of composite nanofiltration membrane: PEG solute transfer method was used for measurement. The detailed steps are as follows:

[0144] (i) Testing the retention rate of composite membranes for PEG with different molecular sizes;

[0145] (ii) Linear fitting was performed between PEG size and retention rate in a logarithmic-probability coordinate system, and the PEG size corresponding to 50% retention rate was the average pore size of the composite membrane.

[0146] (8) Zeta potential test of membrane surface: The test was performed using a Surpass electrokinetic analyzer (Anton Paar). The circulating fluid was a dilute aqueous solution of KCl and the pH of the test fluid was 7.

[0147] (9) The thickness of each layer in the composite nanofiltration membrane was measured using a scanning electron microscope (SEM), model of which was Hitachi S-4800.

[0148] In addition, in the following examples and comparative examples:

[0149] Branched polyethyleneimine (weight-average molecular weight of 25000 g / mol), 1,3,5-benzenetricarboxylic acid chloride, 2-chloroethyltrimethylammonium chloride, 2-bromoethyltrimethylammonium bromide, 3-bromopropyltrimethylammonium bromide, 3-bromopropyltriphenylphosphonium bromide, chloromethyltriphenylphosphonium chloride, iodomethyltriphenylphosphonium iodide, 4-bromomethylbenzyltriphenylphosphonium bromide and iodomethyltrimethylammonium iodide were all purchased from J&K Technology Co., Ltd., and other chemical reagents were purchased from Sinopharm Chemical Reagent Co., Ltd.

[0150] The supporting layer is prepared by a phase inversion method, and the specific steps are as follows:

[0151] A certain amount of polysulfone (number average molecular weight of 80000 g / mol) was dissolved in N,N-dimethylformamide to prepare a polysulfone solution with a concentration of 18 wt%, and degassed at 25°C for 120 min; then, the polysulfone solution was coated on a polyester non-woven fabric (with a thickness of 75 μm) using a scraper to obtain an initial membrane, which was then immersed in water at a temperature of 25°C for 60 min to allow the polysulfone layer on the surface of the polyester non-woven fabric to undergo phase transformation into a porous membrane, and finally washed with water three times to obtain a bottom layer-porous support layer with a total thickness of 115 μm.

[0152] Example 1

[0153] (1) 5 g of polyethyleneimine was dissolved in 100 g of deionized water and heated to 60° C. under stirring; 10 g of 5 wt % 2-bromoethyltrimethylammonium bromide (X and X) was added dropwise to the solution at a rate of 1 mL / min. 1 Br, R 1 ' is ethylene, R 2 '、R 3 '、R 4 After the addition is complete, the reaction is continued at 60° C. for 24 hours. The mass ratio of the polyamine, the halogenated quaternary ammonium salt and the catalyst is 100:10:1.

[0154] (2) The area is 400cm 2 The upper surface of the polysulfone support layer is contacted with 50 mL of a quaternary ammonium salt-modified polyethyleneimine aqueous solution containing 0.5 wt % prepared above, and the liquid is discharged after contacting at 25°C for 60 seconds; then, the upper surface of the support layer is contacted with 30 mL of an Isopar E solution containing 0.1 wt % of 1,3,5-benzenetricarboxylic acid chloride, and the liquid is discharged after contacting at 25°C for 60 seconds; then, the membrane is placed in an oven and heated at 70°C for 3 minutes to obtain a composite nanofiltration membrane N1. Among them, the thickness of the bottom layer in the composite nanofiltration membrane N1 is 75 μm, the thickness of the porous support layer is 40 μm, and the thickness of the polyamide separation layer is 71 nm.

[0155] The Zeta potential, contact angle, nitrogen atom content, phosphorus atom content and average pore size of the surface of composite nanofiltration membrane N1 are shown in Table 1.

[0156] The water flux of the composite nanofiltration membrane N1, the desalination rate of magnesium chloride and lithium chloride, and the magnesium-lithium separation coefficient were tested, and the results are shown in Table 2.

[0157] Figure 1 The schematic diagram of the reaction of primary amine, secondary amine and tertiary amine in the polyethyleneimine molecular chain with 2-bromoethyltrimethylammonium bromide is shown in FIG. Figure 1 As shown, under the action of catalyst KOH, 2-bromoethyltrimethylammonium bromide reacts with polyethyleneimine. After removing HBr, the residue of 2-bromoethyltrimethylammonium bromide is connected to polyethyleneimine through the N atom.

[0158] Figure 2 is the infrared absorption spectrum of composite nanofiltration membrane N1 and composite nanofiltration membrane D1, Figure 2 It can be seen that the composite nanofiltration membrane N1 is located at 3300cm -1 The amino characteristic peak at 964 cm -1 The characteristic absorption peak of quaternary ammonium salt group appeared at 240°, which proved that 2-bromoethyltrimethylammonium bromide fully reacted with polyethyleneimine and introduced quaternary ammonium salt group into the polyamide separation layer of composite nanofiltration membrane during interfacial polymerization.

[0159] Figure 3 This is the XPS spectrum of the membrane surface of the composite nanofiltration membrane N1 of Example 1. Figure 4 The XPS spectrum of the membrane surface of the composite nanofiltration membrane D1 of Comparative Example 1 is shown in FIG. Figure 3 and Figure 4 It can be seen that compared with the composite nanofiltration membrane D1, a new signal peak appears on the membrane surface of the composite nanofiltration membrane N1 at a binding energy of 402.5 eV, which corresponds to the signal peak of the quaternary ammonium salt.

[0160] Example 2

[0161] (1) Dissolve 10 g of polyethyleneimine in 100 g of deionized water and heat to 60° C. under stirring; add 5 g of an aqueous solution containing 1 wt% 2-bromoethyltrimethylammonium bromide and 0.1 wt% sodium hydroxide to the solution at a rate of 1 mL / min. After the addition is complete, keep the temperature at 60° C. and continue the reaction for 24 hours. The mass ratio of the polyamine, the quaternary ammonium halogenide and the catalyst is 200:10:1.

[0162] (2) The composite nanofiltration membrane N2 was obtained in the same manner as in Example 1. In the composite nanofiltration membrane N2, the thickness of the bottom layer was 75 μm, the thickness of the porous support layer was 40 μm, and the thickness of the polyamide separation layer was 75 nm.

[0163] The Zeta potential, contact angle, nitrogen atom content, phosphorus atom content and average pore size of the composite nanofiltration membrane N2 surface are shown in Table 1.

[0164] The water flux of the composite nanofiltration membrane N2, the desalination rate of magnesium chloride and lithium chloride, and the magnesium-lithium separation coefficient were tested, and the results are shown in Table 2.

[0165] Example 3

[0166] (1) Dissolve 7.5 g of polyethyleneimine in 100 g of deionized water and heat to 60° C. under stirring; add 10 g of an aqueous solution containing 10 wt% 2-bromoethyltrimethylammonium bromide and 1 wt% potassium hydroxide to the solution at a rate of 1 mL / min. After the addition is complete, keep the temperature at 60° C. and continue the reaction for 24 hours. The mass ratio of the polyamine, the quaternary ammonium halogenide and the catalyst is 75:10:1.

[0167] (2) The composite nanofiltration membrane N3 was obtained in the same manner as in Example 1. In the composite nanofiltration membrane N3, the thickness of the bottom layer was 75 μm, the thickness of the porous support layer was 40 μm, and the thickness of the polyamide separation layer was 68 nm.

[0168] The Zeta potential, contact angle, nitrogen atom content, phosphorus atom content and average pore size of the surface of composite nanofiltration membrane N3 are shown in Table 1.

[0169] The water flux of the composite nanofiltration membrane N3, the desalination rate of magnesium chloride and lithium chloride, and the magnesium-lithium separation coefficient were tested, and the results are shown in Table 2.

[0170] Example 4

[0171] The preparation method is the same as that of Example 1, except that 2-chloroethyltrimethylammonium chloride (X and X 1 Cl, R 1 ' is ethylene, R 2 '、R 3 '、R 4 ' is methyl) to replace 2-bromoethyltrimethylammonium bromide to obtain a composite separation membrane N4. Among them, the thickness of the bottom layer in the composite nanofiltration membrane N4 is 75 μm, the thickness of the porous support layer is 40 μm, and the thickness of the polyamide separation layer is 82 nm.

[0172] The Zeta potential, contact angle, nitrogen atom content, phosphorus atom content and average pore size of the surface of composite nanofiltration membrane N4 are shown in Table 1.

[0173] The water flux of the composite nanofiltration membrane N4, the desalination rate of magnesium chloride and lithium chloride, and the magnesium-lithium separation coefficient were tested, and the results are shown in Table 2.

[0174] Example 5

[0175] The preparation method is the same as that of Example 1, except that 3-bromopropyltrimethylammonium bromide (X and X 1 Br, R 1 ' is propylene, R 2 '、R 3 '、R 4 ' is methyl) to replace 2-bromoethyltrimethylammonium bromide to obtain composite nanofiltration membrane N5. Among them, the thickness of the bottom layer in the composite nanofiltration membrane N5 is 75 μm, the thickness of the porous support layer is 40 μm, and the thickness of the polyamide separation layer is 72 nm.

[0176] The Zeta potential, contact angle, nitrogen atom content, phosphorus atom content and average pore size of the surface of composite nanofiltration membrane N5 are shown in Table 1.

[0177] The water flux of the composite nanofiltration membrane N5, the desalination rate of magnesium chloride and lithium chloride, and the magnesium-lithium separation coefficient were tested, and the results are shown in Table 2.

[0178] Example 6

[0179] The preparation method is the same as that of Example 1, except that iodomethyltrimethylammonium iodide (X and X 1 I, R 1 ' is methylene, R 2 '、R 3 '、R 4 ' is methyl) to replace 2-bromoethyltrimethylammonium bromide to obtain composite nanofiltration membrane N6. Among them, the thickness of the bottom layer in the composite nanofiltration membrane N6 is 75 μm, the thickness of the porous support layer is 40 μm, and the thickness of the polyamide separation layer is 78 nm.

[0180] The Zeta potential, contact angle, nitrogen atom content, phosphorus atom content and average pore size of the surface of composite nanofiltration membrane N6 are shown in Table 1.

[0181] The water flux of the composite nanofiltration membrane N6, the desalination rate of magnesium chloride and lithium chloride, and the magnesium-lithium separation coefficient were tested, and the results are shown in Table 2.

[0182] Example 7

[0183] The preparation method is the same as that in Example 1, except that 3-bromopropyltriphenylphosphonium bromide (in Formula IV, R 5 ' is propylene, R 6 '、R 7 '、R 8 ' is phenyl, X 1 and X is Br) to replace 2-bromoethyltrimethylammonium bromide to obtain a composite nanofiltration membrane N7. The thickness of the bottom layer in the composite nanofiltration membrane N7 is 75 μm, the thickness of the porous support layer is 40 μm, and the thickness of the polyamide separation layer is 85 nm.

[0184] The Zeta potential, contact angle, nitrogen atom content, phosphorus atom content and average pore size of the composite nanofiltration membrane N7 surface are shown in Table 1.

[0185] The water flux of the composite nanofiltration membrane N7, the desalination rate of magnesium chloride and lithium chloride, and the magnesium-lithium separation coefficient were tested, and the results are shown in Table 2.

[0186] Figure 5 The schematic diagram of the reaction of primary amine, secondary amine and tertiary amine in the polyethyleneimine molecular chain with 3-bromopropyltriphenylphosphonium bromide is shown in FIG. Figure 5 As shown, under the action of catalyst KOH, 3-bromopropyltriphenylphosphonium bromide reacts with polyethyleneimine. After removing HBr, the residue of 3-bromopropyltriphenylphosphonium bromide is connected to polyethyleneimine through the N atom.

[0187] Figure 6 is the infrared spectrum of composite nanofiltration membrane N7 and composite nanofiltration membrane D1. Figure 6 It can be seen that the composite nanofiltration membrane N7 has a -1 The absorption peak corresponding to CP appears at , proving that the quaternary phosphonium salt group exists in the polyamide separation layer.

[0188] Figure 7 This is the XPS spectrum of the composite nanofiltration membrane N7 surface. The signal peak at the binding energy of 132 eV corresponds to the quaternary phosphonium group in the polyamide separation layer.

[0189] Example 8

[0190] The preparation method is the same as that in Example 1, except that chloromethyl triphenylphosphonium chloride (in Formula IV, R 5 ' is methylene, n is 1, R 6 '、R 7 '、R 8 ' is phenyl, X 1 and X is Cl)) to replace 2-bromoethyltrimethylammonium bromide to obtain a composite nanofiltration membrane N8. Among them, the thickness of the bottom layer in the composite nanofiltration membrane N8 is 75 μm, the thickness of the porous support layer is 40 μm, and the thickness of the polyamide separation layer is 83 nm.

[0191] The Zeta potential, contact angle, nitrogen atom content, phosphorus atom content and average pore size of the surface of composite nanofiltration membrane N8 are shown in Table 1.

[0192] The water flux of the composite nanofiltration membrane N8, the desalination rate of magnesium chloride and lithium chloride, and the magnesium-lithium separation coefficient were tested, and the results are shown in Table 2.

[0193] Example 9

[0194] The preparation method is the same as that in Example 1, except that iodomethyl triphenylphosphonium iodide (in Formula IV, R 5 ' is methylene, n is 1, R 6 '、R 7 '、R 8 ' is phenyl, X 1 and X is I) replacing 2-bromoethyltrimethylammonium bromide to obtain a composite nanofiltration membrane N9. The thickness of the bottom layer in the composite nanofiltration membrane N9 is 75 μm, the thickness of the porous support layer is 40 μm, and the thickness of the polyamide separation layer is 88 nm.

[0195] The Zeta potential, contact angle, nitrogen atom content, phosphorus atom content and average pore size of the surface of composite nanofiltration membrane N9 are shown in Table 1.

[0196] The water flux of the composite nanofiltration membrane N9, the desalination rate of magnesium chloride and lithium chloride, and the magnesium-lithium separation coefficient were tested, and the results are shown in Table 2.

[0197] Example 10

[0198] The preparation method is the same as that of Example 1, except that 4-bromomethylbenzyltriphenylphosphonium bromide (in Formula IV, R 5 'for n is 1, R 6 '、R 7 '、R 8 ' is phenyl, X1 and X are Br) replace 2-bromoethyltrimethylammonium bromide to obtain a composite nanofiltration membrane N10. Among them, the thickness of the bottom layer in the composite nanofiltration membrane N10 is 75 μm, the thickness of the porous support layer is 40 μm, and the thickness of the polyamide separation layer is 92 nm.

[0199] The Zeta potential, contact angle, nitrogen atom content, phosphorus atom content and average pore size of the surface of the composite nanofiltration membrane N10 are shown in Table 1.

[0200] The water flux of the composite nanofiltration membrane N10, the desalination rate of magnesium chloride and lithium chloride, and the magnesium-lithium separation coefficient were tested, and the results are shown in Table 2.

[0201] Embodiment 11

[0202] (1) 5 g of polyethyleneimine was dissolved in 100 g of deionized water and heated to 60° C. under stirring; 10 g of 2.5 wt% 2-bromoethyltrimethylammonium bromide (X and X) was added dropwise to the solution. 1 Br, R 1 ' is ethylene, R 2 '、R 3 '、R 4 ' is methyl) and 2.5wt% 3-bromopropyltriphenylphosphonium bromide (in Formula IV, R 5' is propylene, R 6 '、R 7 '、R 8 ' is phenyl, X 1 and X is Br) and 0.5wt% potassium hydroxide aqueous solution, after the addition is complete, the reaction is continued at 60°C for 24 hours. The mass ratio of the polyamine, the halogenated quaternary ammonium salt, the halogenated quaternary phosphonium salt and the catalyst is 100:5:5:1.

[0203] (2) The same method as in Example 1 was used to obtain a composite nanofiltration membrane N11, wherein the thickness of the bottom layer in the composite nanofiltration membrane N11 was 75 μm, the thickness of the porous support layer was 40 μm, and the thickness of the polyamide separation layer was 79 nm.

[0204] The Zeta potential, contact angle, nitrogen atom content, phosphorus atom content and average pore size of the surface of the composite separation membrane N11 are shown in Table 1.

[0205] The water flux of the composite nanofiltration membrane N11, the desalination rate of magnesium chloride and lithium chloride, and the magnesium-lithium separation coefficient were tested, and the results are shown in Table 2.

[0206] Example 12

[0207] The preparation method is the same as that in Example 1, except that in step (1), the mass ratio of the polyamine, the halogenated quaternary ammonium salt and the catalyst is 0.5:0.5:0.05=10:10:1, and a composite nanofiltration membrane N12 is obtained. Among them, the thickness of the bottom layer in the composite nanofiltration membrane N12 is 75 μm, the thickness of the porous support layer is 40 μm, and the thickness of the polyamide separation layer is 80 nm.

[0208] The Zeta potential, contact angle, nitrogen atom content, phosphorus atom content and average pore size of the surface of composite nanofiltration membrane N12 are shown in Table 1.

[0209] The water flux of the composite nanofiltration membrane N12, the desalination rate of magnesium chloride and lithium chloride, and the magnesium-lithium separation coefficient were tested, and the results are shown in Table 2.

[0210] Comparative Example 1

[0211] The upper surface of the polysulfone support layer was contacted with 50 mL of an aqueous solution containing 0.5 wt% polyethyleneimine, and the solution was drained after contacting at 25°C for 60 seconds; then, the upper surface of the support layer was contacted with 30 mL of an Isopar E solution containing 0.1 wt% 1,3,5-benzenetricarboxylic acid chloride, and the solution was drained after contacting at 25°C for 60 seconds; then, the membrane was placed in an oven and heated at 70°C for 3 minutes to obtain a composite nanofiltration membrane D1. Among them, the thickness of the bottom layer in the composite nanofiltration membrane D1 is 75 μm, the thickness of the porous support layer is 40 μm, and the thickness of the polyamide separation layer is 85 nm.

[0212] The Zeta potential, contact angle and average pore size of the composite nanofiltration membrane D1 surface are shown in Table 1.

[0213] The water flux of the composite nanofiltration membrane D1, the salt rejection rate of magnesium chloride and lithium chloride, and the magnesium-lithium separation coefficient were tested, and the results are shown in Table 2.

[0214] Table 1

[0215]

[0216]

[0217] Note: a - The content of nitrogen atoms in the quaternary ammonium salt group; b -The content of phosphorus atoms in composite nanofiltration membranes.

[0218] Table 2

[0219]

[0220] It can be seen from Tables 1 and 2 that compared with the composite nanofiltration membrane D1, in the composite nanofiltration membranes N1-N12 prepared in the embodiment, due to the introduction of quaternary ammonium salt groups and / or quaternary phosphonium salt groups, the interfacial polymerization is regulated, so that the interfacial polymerization reaction is more sufficient, resulting in a denser separation layer of the composite nanofiltration membrane and a smaller pore size, thereby improving the retention rate of magnesium chloride and the magnesium-lithium separation efficiency.

[0221] On the other hand, the halogenated quaternary ammonium salt and / or quaternary phosphonium salt reacts biochemically with the polyamine under the action of an alkaline catalyst, and the positively charged quaternary ammonium salt groups and / or quaternary phosphonium salt groups are modified into the polyamine molecules, so that after interfacial polymerization, the positive charge density on the surface of the composite nanofiltration membrane is increased, and the retention effect of the composite nanofiltration membrane on magnesium ions is improved through the repulsion effect between the positive charges, thereby improving the magnesium-lithium separation efficiency.

[0222] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite nanofiltration membrane, characterized in that: The composite nanofiltration membrane comprises a bottom layer, a porous support layer and a polyamide separation layer in sequence; Wherein, the polyamide separation layer is grafted with quaternary ammonium salt groups and / or quaternary phosphonium salt groups via N atoms; The quaternary ammonium salt group has a structure shown in Formula I; the quaternary phosphonium salt group has a structure shown in Formula II and / or Formula III; wherein R1 is a substituted or unsubstituted alkylene group of C1-C9; R2, R3 and R4 are each independently selected from a C1-C3 alkyl group or a phenyl group; R5 is a C1-C6 alkylene group, a phenyl group or a C7-C10 aralkyl group; R6, R7 and R8 are each independently selected from a phenyl group or a C7-C10 aralkyl group; R9, R 10 and R 11 Each is independently a phenyl group or a C7-C10 aralkyl group, and n is an integer of 0-3; X, X1 and X2 are each independently halogen.

2. The composite nanofiltration membrane according to claim 1, wherein R1 is a C1-C6 substituted or unsubstituted alkylene or phenyl group, R2, R3 and R4 are each independently CH3; R5 is a C1-C3 alkylene, phenyl or C8-C9 aralkyl group; R6, R7 and R8 are each independently phenyl; R9, R 10 and R 11 Each is independently phenyl, and n is an integer of 0-3; Preferably, R1 is a C1-C3 substituted alkylene group, wherein the substituent is a hydroxyl group or a carboxyl group; Preferably, X is Cl, Br or I; X1 and X2 are each independently F, Cl, Br or I.

3. The composite nanofiltration membrane according to claim 1 or 2, wherein: The content of nitrogen atoms in the quaternary ammonium salt groups in the composite nanofiltration membrane is 1-5 at.%, preferably 2-5 at.%; Preferably, the content of phosphorus atoms in the composite nanofiltration membrane is 0.4-3 at.%, preferably 0.5-2 at.%.

4. The composite nanofiltration membrane according to any one of claims 1 to 3, wherein: The surface Zeta potential of the composite nanofiltration membrane is -5 mV to 15 mV, preferably 0 mV to 10 mV.

5. The composite nanofiltration membrane according to any one of claims 1 to 4, wherein: The average pore size of the composite nanofiltration membrane is 0.1-0.5 nm, preferably 0.15-0.35 nm.

6. The composite nanofiltration membrane according to any one of claims 1 to 5, wherein: The contact angle of the composite nanofiltration membrane is 30-80°, preferably 30-60°.

7. The composite nanofiltration membrane according to any one of claims 1 to 6, wherein: The thickness of the bottom layer is 30-150 μm, preferably 50-120 μm; Preferably, the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm; Preferably, the thickness of the polyamide separation layer is 10-500 nm, preferably 50-300 nm.

8. A method for preparing a composite nanofiltration membrane, characterized in that: The preparation method comprises the following steps: S1. Under stirring, adding a first solution containing a quaternary ammonium halogenate salt and / or a quaternary phosphonium halogenate salt and a catalyst to a second solution containing a polyamine to react and obtain a modified polyamine; S2, preparing a porous supporting layer on the bottom layer; S3, bringing the surface of the porous support layer into first contact with the aqueous phase containing the modified polyamine in step S1, and then bringing it into second contact with the organic phase containing polyacyl chloride, and then subjecting it to heat treatment to obtain the composite nanofiltration membrane; The halogenated quaternary ammonium salt has a structure shown in Formula IV; the halogenated quaternary phosphonium salt has a structure shown in Formula V or VI; wherein R1' is a C1-C9 substituted or unsubstituted alkylene group; R2', R3' and R4' are each independently selected from a C1-C3 alkyl group or a phenyl group; R5' is a C1-C6 alkylene group, a phenyl group or a C7-C10 aralkyl group; R6', R7' and R8' are each independently selected from a phenyl group or a C7-C10 aralkyl group; n is an integer of 0-3; R9', R 10 ' and R 11 'Each independently is phenyl or C7-C10 aralkyl; X1, X2, X3 and X are each independently halogen.

9. The preparation method according to claim 8, wherein: R1' is a substituted or unsubstituted alkylene of C1-C6; R2', R3' and R4' are each independently CH3; R5' is a C1-C3 alkylene, phenyl or C8-C9 aralkyl; R6', R7' and R8' are each independently phenyl; n is an integer of 0-3; R9', R 10 ' and R 11 ' are each independently phenyl; Preferably, R1' is a C1-C3 substituted alkylene group, wherein the substituent is a hydroxyl group or a carboxyl group; Preferably, X is Cl, Br or I; Preferably, X1, X2 and X3 are each independently F, Cl, Br or I.

10. The preparation method according to claim 8 or 9, wherein: In step S1, the halogenated quaternary ammonium salt is selected from at least one of 2-chloroethyltrimethylammonium chloride, 2-chloroethyltriethylammonium chloride, 2-chloroethyltriphenylammonium chloride, 3-chloro-2-hydroxypropyltrimethylammonium chloride, 3-chloropropyltrimethylammonium chloride, 4-chlorobutyltrimethylammonium chloride, 5-chloropentyltrimethylammonium chloride, 6-chlorohexyltrimethylammonium chloride, 2-bromoethyltrimethylammonium bromide, 3-bromopropyltrimethylammonium bromide, 4-bromobutyltrimethylammonium bromide, 5-bromopentyltrimethylammonium bromide, 6-bromohexyltrimethylammonium bromide, iodomethyltrimethylammonium iodide, 2-iodoethyltrimethylammonium iodide, 3-iodopropyltrimethylammonium iodide, 4-iodobutyltrimethylammonium iodide, 5-iodopentyltrimethylammonium iodide and 6-iodohexyltrimethylammonium iodide; Preferably, the halogenated quaternary phosphonium salt is selected from 3-bromopropyl triphenyl phosphonium bromide, 2-bromoethyl triphenyl phosphonium bromide, 1-bromoethyl triphenyl phosphonium bromide, bromomethyl triphenyl phosphonium bromide, 3-chloropropyl triphenyl phosphonium chloride, 2-chloroethyl triphenyl phosphonium chloride, 1-chloroethyl triphenyl phosphonium chloride, chloromethyl triphenyl phosphonium chloride, 3-iodopropyl triphenyl phosphonium iodide, 2-iodoethyl triphenyl phosphonium iodide, 1-iodoethyl triphenyl phosphonium iodide, iodomethyl triphenyl phosphonium bromide, (3,3,3-trichloropropyl) triphenyl phosphonium chloride, 4-bromo At least one of methylbenzyltriphenylphosphonium bromide, (bromodifluoromethyl)triphenylphosphonium bromide, 2-bromomethylbenzyltriphenylphosphonium bromide, 3-bromomethylbenzyltriphenylphosphonium bromide, 4-chloromethylbenzyltriphenylphosphonium chloride, 2-chloromethylbenzyltriphenylphosphonium chloride, 3-chloromethylbenzyltriphenylphosphonium chloride, 4-iodomethylbenzyltriphenylphosphonium iodide, 2-iodomethylbenzyltriphenylphosphonium iodide and 3-iodomethylbenzyltriphenylphosphonium iodide; preferably 3-bromopropyltriphenylphosphonium bromide and / or 4-bromomethylbenzyltriphenylphosphonium bromide; Preferably, the catalyst is selected from at least one of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, potassium bicarbonate, disodium hydrogen phosphate and dipotassium hydrogen phosphate; Preferably, the concentration of the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the first solution is 0.5wt%-20wt%, preferably 1wt%-10wt%; Preferably, the concentration of the catalyst in the first solution is 0.01 wt%-5 wt%, preferably 0.1 wt%-1 wt%.

11. The preparation method according to any one of claims 9 to 10, wherein: In step S1, the polyamine is selected from at least one of polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, polyethylenepolyamine, piperazine, m-phenylenediamine and p-phenylenediamine; preferably polyethyleneimine and / or polyethylenepolyamine; Preferably, the concentration of the polyamine in the second solution is 1wt%-20wt%, preferably 5wt%-10wt%; Preferably, the amounts of the first solution and the second solution are such that the mass ratio of the polyamine, the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt, and the catalyst is 1-500:1-100:

1.

12. The preparation method according to any one of claims 8 to 11, wherein: The reaction conditions include: reaction temperature of 25-90°C, preferably 40-60°C; reaction time of 1-48h, preferably 6-24h; Preferably, the first solution is added dropwise to the second solution containing the polyamine; Preferably, the dropping speed is 0.5-5 mL / min.

13. The preparation method according to any one of claims 8 to 12, wherein: In step S3, the first contact time is 5-100 s, preferably 10-60 s; Preferably, the second contact time is 10-200s, preferably 20-120s; Preferably, the heat treatment conditions include: heat treatment temperature of 40-150° C., preferably 50-120° C.; heat treatment time of 0.5-10 min, preferably 1-5 min.

14. The preparation method according to any one of claims 8 to 13, wherein: In step S3, the polyacyl chloride is selected from at least one of 1,3,5-benzene trimethylene dicarboxylic acid chloride, 1,2-phthaloyl chloride, 1,3-phthaloyl chloride, 1,4-phthaloyl chloride and adipoyl chloride, preferably 1,3,5-benzene trimethylene dicarboxylic acid chloride and / or 1,4-phthaloyl chloride; Preferably, the concentration of the modified polyamine in the aqueous phase is 0.1wt%-5wt%, preferably 0.5wt%-2wt%; Preferably, the concentration of the polyacid chloride in the organic phase is 0.01 wt%-1 wt%, preferably 0.1-0.5 wt%.

15. A composite nanofiltration membrane prepared by the preparation method according to any one of claims 8 to 14.

16. Use of the composite nanofiltration membrane according to any one of claims 1 to 7 and 15 in the field of water treatment and separation.

Citation Information

Patent Citations

  • Anti-biological contamination reverse osmosis membrane, and preparation method and application thereof

    CN110354682A

  • Method for preparing composite nanofiltration membrane by using multi-component buffer system

    CN111450714A

  • Quaternary phosphonium salt antibacterial polyamide water treatment membrane and preparation method thereof

    CN112121646A

  • Polyamide composite membrane and preparation method thereof

    CN115155338A

  • High-performance thin-film composite nanofiltration membrane as well as preparation method and application thereof

    CN115337801A